2007
DOI: 10.1097/hjr.0b013e3282eeb308
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cardiovascular risk factors and their implications in subsequent birth cohorts of older adults in Germany: a life course approach

Abstract: Women and men reaching old age in the forthcoming years have more unfavourable lifetime risk factor profiles than earlier birth cohorts. These patterns might have substantial implications for the future burden of chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 23 publications
3
57
0
2
Order By: Relevance
“…A further strength of the ESTHER study is its representativeness of a population that attends screenings. Nevertheless, the distribution of sociodemographic baseline characteristics and common prevalent chronic diseases in our study were similar to the distribution in the respective age categories in the German National Health Survey, which is a representative sample of the German population [21,22], a fact supporting the external validity of our study. FPG screening has been performed under conditions of routine medical practice.…”
Section: Risk For Incident Cardiovascular Eventssupporting
confidence: 81%
See 1 more Smart Citation
“…A further strength of the ESTHER study is its representativeness of a population that attends screenings. Nevertheless, the distribution of sociodemographic baseline characteristics and common prevalent chronic diseases in our study were similar to the distribution in the respective age categories in the German National Health Survey, which is a representative sample of the German population [21,22], a fact supporting the external validity of our study. FPG screening has been performed under conditions of routine medical practice.…”
Section: Risk For Incident Cardiovascular Eventssupporting
confidence: 81%
“…Study design This investigation is based on the 'Epidemiologische Studie zu Chancen der Verhütung, Früherkennung und optimierten Therapie chronischer Erkrankungen in der älteren Bevölkerung' [Epidemiological investigations of the chances of preventing, recognising early and optimally treating chronic diseases in an elderly population] (ESTHER) study, an ongoing cohort study, details of which have been reported elsewhere [21,22]. Briefly, 9,949 individuals, aged 50-74 years at baseline, were recruited by their general practitioners during a routine health check-up between 2000 and 2002 in the German federal state of Saarland.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 9,949 participants, ages 50 to 74 years at baseline, were enrolled during a routine physician health checkup between 2000 and 2002. The distribution of sociodemographic characteristics, prevalent diseases, and major risk factors in the ESTHER study are comparable with those in the German National Health Survey which was conducted in a representative sample of the German population in 1998 (30). Blood samples were drawn during the health checkup, centrifuged, sent to the study center, and finally stored at À80 C until measurement.…”
Section: Study Design and Study Populationmentioning
confidence: 75%
“…Detailed information on the study design and the study population has been reported elsewhere [13,14]. Briefly, baseline assessment was conducted between July 2000 and December 2002 and included 9,949 participants aged 50-75 years, recruited by their general practitioner.…”
Section: Methodsmentioning
confidence: 99%